Attainable accuracy of gas turbine engine housing ring machining - Старовоитов S. V.; Саттаров M. E. (Materials. Technologies. Design, 2020)
The problems of achievable accuracy of machining of casing rings of gas turbine engines are described. As a criterion for the machinability of the structure, geometric compliance is proposed. A model for machining the casing rings of gas turbine engines is developed. The values of geometric compliance of real body rings of gas turbine engines are calculated. The values of arising deviations in the processing of real casing rings of gas turbine engines and simulation results are compared. The critical value of geometric compliance has been determined, which reflects the boundary conditions under which it becomes necessary to use non-traditional technological solutions in the field of tools, cutting modes, equipment, etc. to achieve the specified accuracy.